The experiences of mothers of children with food allergy: A qualitative study - Ozturk, Cigdem Sari; Merter, Ozlem Selime; Sengul, Zeynep Kisecik (Elsevier Science Inc, 2023)
Background: Food allergies adversely affect the quality of life of the child and family, as they require lifelong treatment and follow-up. This study aims to examine the experiences of mothers who have children with food allergies within the framework of the biopsychosocial-spiritual model. Methods: This study, using a qualitative research design, was carried out with mothers of children followed up with food allergy in the pediatric allergy outpatient clinic of a university hospital between December 15, 2022 and January 05, 2023. Purposive sampling method was used in the study and semi-structured interviews were conducted with 12 mothers. All interviews were audio recorded and transcribed. Inductive thematic analysis method was used. The study was written based on the COREQ checklist. Findings: Three themes, eight sub-themes, and 19 categories were identified: The effects of the disease on the physical health of the child and mother in the biological effects theme; psychosocial responses to disease, adaptation to treatment, future anxiety, coping strategies, and communication/interaction in the psychosocial effects theme; search for purpose-meaning in life and understanding belief/basic human values in the spiritual effects theme. Discussion: It has been concluded that food allergies affect maternal health extensively, especially in the psychosocial field, and that it affects family relationships, the time that mothers spare for themselves, and physical and spiritual health. Application to practice: The findings will be a guide for improving the quality of life of mothers followed up with food allergies and for the care and counseling support to be provided to mothers.
Keywords: Child; Family; Food allergies